WATER SENSITIVE PAPER AND ALTERNATIVE PHOTOGRAPHIC IN DEPOSITION TESTS OF DROPLETS - Baio, F. H. R.; Scarpin, I. M.; da Silva, E. E. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Many phytotechnical trials involving pesticide application technology used as artificial target for spectrum drops characterization the water sensitive paper. The objective of this study was to compare the results of the VMD, Span index and the percentage of drops smaller than 100 µm obtained by the use of commercial water sensitive and photographic alternative papers related to the particle analyzer by laser diffraction. Three models of spray tips were used: flat fan extended range tip XR11001; flat fan pre-orifice tip LBD11001; and wide angle flat spray tips TT11001. The droplets spectrum characterization was performed by three methods (laser particle analyzer, commercial water sensitive paper and photographic paper) and two application rates (70 and 100 L ha-1). The applied methodologies by the use of commercial water sensitive and alternative photographic papers cannot detect all droplets smaller than 100 µm, very fine droplets (ASAE, 2009), affecting the measurement of VMD (Volume Median Diameter), Span index and percentage of droplets <100 µm in application technology trials using TT, XR and LBD spray tips, and according to the 70 and 100 L ha-1 application rates. The alternative photographic paper likewise characterizes the droplet spectrum regarding to the use of commercial water sensitive paper.